Sustaining Parliamentary Action to Improve Maternal, Newborn and Child Health: Handbook for parliamentarians No. 21 - Siân Long, Dr. Chris Baryomunsi; Senator Thandi Shongwe, Ms. Paula Turyahikayo; Senator Salma Ataullahjan (2016)
Section 1 sets out the importance of parliamentary action if maternal, newborn and child health are to improve. Section 2 provides a summary of the state of maternal, newborn and child health and the related opportunities and challenges that parliamentarians will encounter. Section 3 suggests key actions that parliamentarians – as members of the legislature and as representatives of their populations – can take to provide leadership on maternal, newborn and child health.